Exigência protéica e relação energia/proteína para alevinos de piracanjuba (Brycon orbignyanus) - Sá, Marcelo Vinícius Do Carmo E [UNESP]; Fracalossi, Débora Machado [UNESP] (My University, 2002)
The aim of this study was to determine the dietary protein requirement and associated energy to protein (E/P) ratio for Piracanjuba, Brycon orbignyanus, fingerlings. Casein-gelatin semipurified diets were formulated to contain six crude protein (CP) concentrations: 24, 26, 29, 32, 36 e 42% at one energy level, 3,000 kcal metabolizable energy (ME)/kg. These diets resulted in E/P ratios of 12.3, 11.6, 10.4, 9.2, 8.5 and 7.1 kcal ME/g CP, respectively. The protein, lipid and digestible carbohydrate sources were casein/gelatin, cod liver oil/soybean oil and dextrin, respectively. After an initial 5-day conditioning period, each experimental diet was fed to satiation, twice a day, to 8.38 ± 0.09 g piracanjuba fingerlings (n = 27), housed in eighteen 100-L fiberglass tanks connected to a water recirculating system, and kept at 26.3°C average water temperature (range: 23.7 to 30.2°C). After 90 days, the lowest dietary CP level that produced maximum fish weight gain was 29% CP with associated E/P ratio of 10.4 kcal ME/g CP. Higher dietary CP levels, i.e., 32, 36 and 42% did not improve 29% CP feed conversion, protein efficiency ratio, apparent net protein utilization and gross energy retained. Whole-body fish composition (total lipid and protein concentration) was not affected by the dietary CP level.
Dietary protein requirement and energy to protein ratio for piracanjuba (Brycon orbignyanus) fingerlings
Keywords: Brycon orbignyanus; Energy to protein ratio; Piracanjuba; Protein requirement